Job Termination and Social Security of Migrant Workers in Malaysia During Covid-19 Pandemic - Saidatul Nadia Abd Aziz; Salawati Mat Basir; Moganasundari Mahalingam (Faculty of Law, Universitas Padjadjaran, 2022)
Migrant workers are the most vulnerable groups during the Covid-19 outbreak. The study aims to discuss the current legal framework governing migrant workers in Malaysia during the Covid-19 Pandemic. The discussion covers the effect of the Covid-19 Pandemic on migrant workers focusing on job termination and access to social security protection. It also makes recommendations on policy guidelines to ensure migrant worker’s safety against job termination and zero access to social security during the Covid-19 Pandemic. The study employed a doctrinal approach. It used primary and secondary data that included desktop research, with a particular emphasis on journals, documents, and official reports. Policymakers tended to neglect migrant workers during the pandemic because the migrant workers had less access to adequate security, particularly in terms of job termination and living conditions. The Covid-19 pandemic and the Movement Control Order imposed in Malaysia have affected migrant workers in various ways. It puts workers who are unable to work and who want to work in vital services in jeopardy. In conclusion, a national approach policy is impractical for migrant workers because the workers are short of access to social security and urgent assistance.DOI: https://doi.org/10.22304/pjih.v9n3.a1